Lasting potentiation of inhibition is associated with an increased number of gamma-aminobutyric acid type A receptors activated during miniature inhibitory postsynaptic currents. - Otis, T S (1994)
Whole-cell patch-clamp recordings unveiled a substantial increase in the amplitude, but no change in the frequency, of miniature inhibitory postsynaptic currents (mIPSCs) in dentate gyrus granule cells following chronic epilepsy induced by kindling. This novel and persistent enhancement of gamma-aminobutyric acid type A (GABAA) receptor-mediated inhibition lasted for at least 48 hr following its induction. Nearly a doubling of the number of activated functional postsynaptic GABAA receptor channels during mIPSCs without any change in single-channel conductance or kinetics could be demonstrated using nonstationary fluctuation analysis. As postsynaptic GABAA receptors are likely to be pharmacologically saturated by the transmitter concentration in the cleft, incrementing the number of functional receptor channels may be the most effective means to augment inhibition in the mammalian brain.